Comparative chemical and biological hydrolytic stability of homologous esters and isosteres - Hygor M. R. de Souza; Jéssica S. Guedes; Rosana H. C. N. Freitas; Luis G. V. Gelves; Harold H. Fokoue; Carlos Mauricio R. Sant'Anna; Eliezer J. Barreiro; Lidia M. Lima (Taylor & Francis Group, 2022)
Esters are one of the major functional groups present in the structures of prodrugs and bioactive compounds. Their presence is often associated with hydrolytic lability. In this paper, we describe a comparative chemical and biological stability of homologous esters and isosteres in base media as well as in rat plasma and rat liver microsomes. Our results provided evidence for the hydrolytic structure lability relationship and demonstrated that the hydrolytic stability in plasma and liver microsome might depend on carboxylesterase activity. Molecular modelling studies were performed in order to understand the experimental data. Taken together, the data could be useful to design bioactive compounds or prodrugs based on the correct choice of the ester subunit, addressing compounds with higher or lower metabolic lability.